Islam in Hong Kong : Muslims and Everyday Life in China World City - O'Connor, Paul (Hong Kong culture and society., 2012)
More than a quarter of a million Muslims live and work in Hong Kong. Among them are descendants of families who have been in the city for generations, recent immigrants from around the world, and growing numbers of migrant workers. Islam in Hong Kong explores the lives of Muslims as ethnic and religious minorities in this unique postcolonial Chinese city. Drawing on interviews with Muslims of different origins, O'Connor builds a detailed picture of daily life through topical chapters on language, space, religious education, daily prayers, maintaining a halal diet in a Chinese environment, racism, and other subjects. Although the picture that emerges is complex and ambiguous, one striking conclusion is that Muslims in Hong Kong generally find acceptance as a community and do not consider themselves to be victimised because of their religion.